Innovation and the arts : the value of humanities studies for business - Formica, Piero; Edmondson, John (Emerald Publishing Limited, 2020)
We live in the Age of Knowledge but we are heading towards the Age of Imagination. However, our current education systems still divide arts and business, juxtaposing them as different worlds, apparently ignoring the essential truth that imagination is the springboard of innovation. For business to continue to evolve, the barriers to creativity and innovation must be lowered. In Innovation and the Arts: The Value of Humanities Studies for Business, editors Piero Formica and John Edmondson bring together a cast of expert contributors to explore how arts education can transform future business and social endeavours by developing empathy and enhancing skills frequently identified as lacking in graduates entering the workplace. Looking at arts and humanities across the broad spectrum of business and social innovation, and in the context of business education, examples of entrepreneurial and innovative developments, and the nature of the innovative mind, the contributors show how underdeveloped empathy and creativity constrain innovation. Art is disruptive, and innovation requires disruption to thrive. By dwelling on the need for the convergence of business, innovation and the arts, Innovation and the Arts highlights the inestimable value of lowering the psychological, organizational and institutional barriers that keep them apart. For educators and practitioners, this is an in-depth discussion designed to stimulate awareness of the issues facing business education.
Includes index.
Keywords: Business education.; Humanities -- Economic aspects.; Business & Economics -- Education.; Industrial or vocational training.; elektronické knihy; electronic books